2016
DOI: 10.1007/s41348-016-0052-x
|View full text |Cite
|
Sign up to set email alerts
|

Thrips (Thysanoptera) associated with two genetically modified types of linseed (Linum usitatissimum L.)

Abstract: The aim of this study was to determine thrips abundance, species composition and seasonal dynamics on two genetically modified types of linseed, i.e., overproducing flavonoids, overproducing glycoside derivatives of phenylpropanoids and the respective non-modified, control plants with concentrations of phenylpropanoids typical for this variety. The experiment was conducted near Wrocław, Poland, in 2011-2013. For the determination of thrips species composition, 10 plants were collected from plots when linseed p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…In a population of F. intonsa in flowers of food legume plants, participation of males was even higher, with a sex ratio of over 79% Pobożniak (2011). Hurej et al (2015), in their analysis of thrips settlement on both forms of Andean lupine, pointed out that in the case of flower thrips, the morphological form of the plant did not affect the occurrence of male thrips, and the calculated sex ratio was 86.2%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a population of F. intonsa in flowers of food legume plants, participation of males was even higher, with a sex ratio of over 79% Pobożniak (2011). Hurej et al (2015), in their analysis of thrips settlement on both forms of Andean lupine, pointed out that in the case of flower thrips, the morphological form of the plant did not affect the occurrence of male thrips, and the calculated sex ratio was 86.2%.…”
Section: Discussionmentioning
confidence: 99%
“…In our experiment, the sex ratio of this species on A. cepa and A. fistulosum was about 96.8% and 79.0% on onion and about 87.5% and 84.7% on Welsh onion in 2015 and 2016, respectively (Table 4). Hurej et al (2017) reported that the sex ratio of A. intermedius on linseed ranged from 61.5% to 77.1%, but never exceeded 80%. In turn, on peas, beans, lentil, French beans or soya beans, the percentage of males in the population of A. intermedius was lower, and the sex ratio ranged from 82.4% to 89.6% (Pobożniak, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…However, biochemical-based defence is considered more effective as it directly affects insect growth and development [12]. It has been reported that many secondary metabolites and plant hormones are associated with thrips resistance, such as protease inhibitors, phenols, tannins, salicylic acid (SA) and jasmonic acid (JA) [13][14][15][16] Since there is an increasing focus on improving crop production through safe and sustainable means by reducing the reliance on pesticides [17], the use of resistant cultivars is currently considered the most effective and environmentally sustainable strategy to control insects. Alfalfa cultivars are heterogeneous populations, and recurrent selection is highly heritable and it is relatively easy to accumulate excellent genes through a large population.…”
Section: Introductionmentioning
confidence: 99%
“…Feeding by these insects causes characteristic changes in the appearance of the affected tissues. Some species also transmit plant diseases [1,2]. A small number of species in Thysanoptera, especially within the Aelothripidae family, are predatory, feeding on small invertebrates such as mites, other thrips and the larvae of some insects [3].…”
Section: Introductionmentioning
confidence: 99%